Respon Perkecambahan Benih Aren (Arenga pinnata Merr) Terhadap Lama Penyimpanan pada Media Simpan Serbuk Gergaji - Hildegardis Dahut; Mamie Elsyana Pellondo’u; Astin Elise Mau (Wana Lestari, 2023)
Arena (Arenga pinnata Merr) is one of the plants included in NTFPs (Non-Timber Forest Products) that has benefits for all parts of the plant. One of the factors that affects seed germination is the storage medium. Sawdust is one of the commonly used storage media because sawdust has the ability to store water and maintain humidity around seeds. This study aims to determine the effect of sawdust storage media on the germination of arena seeds. This research was conducted from Mai to August 2022 in Pong Murung Village, Ruteng District, Manggarai Regency. The experimental device used was a completely randomized device (CRD) using a single factor, namely storage time (0, 1, 2, 3, 4, weeks). The results showed that seed storage time had a very significant effect on research parameters, including seed moisture content, germination percentage, and germination rate. Storage for 2 weeks is a storage that has a different effect from other storage periods for the parameters of germination percentage and germination rate.